2017
DOI: 10.4103/jets.jets_103_16
|View full text |Cite
|
Sign up to set email alerts
|

Lactate clearance as the predictor of outcome in pediatric septic shock

Abstract: Context:Septic shock can rapidly evolve into multiple system organ failure and death. In the recent years, hyperlactatemia has been found to be a risk factor for mortality in critically ill adults.Aims:To evaluate the predictive value of lactate clearance and to determine the optimal cut-off value for predicting outcome in children with septic shock.Settings and Design:A prospective observational study was performed on children with septic shock admitted to pediatric Intensive Care Unit (PICU).Subjects and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…It is likely that risk stratification based on pre-existing factors allows for earlier identification of patients at risk, well before deviation of vital signs. In our study population, abnormal lactate and/or pH could identify 20% of patients at risk, consistent with various previous studies supporting the use of lactate as a predictor in pediatric patients with sepsis [6, 14, 22]. It should be noted that these results do not validate these laboratory tests as screening tools in the general population, but should be put in perspective as a tool to raise situational awareness in risk patients.…”
Section: Discussionsupporting
confidence: 80%
“…It is likely that risk stratification based on pre-existing factors allows for earlier identification of patients at risk, well before deviation of vital signs. In our study population, abnormal lactate and/or pH could identify 20% of patients at risk, consistent with various previous studies supporting the use of lactate as a predictor in pediatric patients with sepsis [6, 14, 22]. It should be noted that these results do not validate these laboratory tests as screening tools in the general population, but should be put in perspective as a tool to raise situational awareness in risk patients.…”
Section: Discussionsupporting
confidence: 80%
“…In another study, Kurade and Dhanawade in their study reported fever as the most common presenting symptom and predictor of mortality associated with sepsis [7]. Choudhary et al furthermore identified younger age, low GCS at admission, need of mechanical ventilation and a shorter duration of hospital stay, to be significantly associated with mortality among pediatric septic shock patients [8]. In this study, however, it was observed that none of the presenting symptoms were statistically significant predictors of mortality.…”
Section: Discussionmentioning
confidence: 49%
“…Compared to this, the present study was conducted for 6 months only. Kaur et al in their study reported it as 58% [2] On the other hand, Choudhary et al [8] found it as 63.5%. These high mortality rates in different studies indicate sepsis as one of the leading causes of death in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…India), clearly representing significantly different populations. [9][10][11][12][13] In a large observational cohort study of 1299 children with suspected sepsis presenting to a US ED, 9 those with initial lactate >4 mmol/L had higher 30-day mortality (4.8% vs 1.7%). However, it is important to note that, in this patient group with a low mortality overall (1.9%), 80% (20/25) of all deaths were in children with initial lactate <4 mmol/L and >95% patients with lactate >4 mmol/L survived, yielding a sensitivity of only 20%.…”
Section: Interpretationsmentioning
confidence: 99%
“…In a study of 700 medical PICU admissions, 17 persistent hyperlactataemia (>2 mmol/L) at 24 hours was associated with 93% mortality versus 30% in children whose lactate levels normalised (sensitivity 78%, specificity 89%, LR+ 7, LR− 0.25); this compared with 64% mortality in children with admission hyperlactataemia versus 6% in children without. Two studies address persistent hyperlactataemia at 24 hours in children with septic shock admitted to PICUs in India: Choudhary et al (n=148) observed that lactate levels falling <10% were associated with 83.1% (74/89) mortality versus 33.9% (20/59) in children whose lactate normalised more rapidly 12 ; Nazir et al reported that children whose lactate failed to fall by >20% at 24 hours had 100% (28/28) 60-day mortality versus 8.3% (7/84) in those whose lactate reduced by >20%. 15 This association was evident even at 6 hours: mortality 83.3% versus 17.05% (sensitivity 94.8%, specificity 57.1%, LR+ 2.21, LR− 0.091).…”
Section: In Children With Suspected Sepsis Does Lowering Lactate Levels Improve Outcomes?mentioning
confidence: 99%